Administração discursiva nas bibliotecas universitárias brasileiras - Faury, Simone Dib (2013)
It proposes discursive administration in brazilian academic libraries which is considered a current forms of administration alternative. It discusses the main features of the information society and the technological developments and the impacts on education, especially in universities, to contextualize the changes in academic libraries. It presents main aspects of theories of Communicative Action and Discourse of Jürgen Habermas and the basic assumptions of discourse administration, from these theories. It addresses the management of academic libraries, based on the literature, aiming to show brief history on the subject. It presents the results of empirical research shown in the oral communications of the National Seminar of University Libraries in the years of 2004, 2008 and 2012 that report forms of administration used in these libraries. The results reveal that most forms of administration in that period is related to contemporary approaches in the area of administration, indicating linkage between this area and Librarianship; 36% of the universe analyzed come under some aspect, the focus on technology and 23% in the communicative approach; the administration discursive assumptions not identified the universe analyzed, and finally it suggests the predominance of instrumental rationality in these organizations. It presents general guidelines for discourse administration in brazilian university libraries in order to offer help to the managers of these libraries and to encourage reflection and debate on the administration of libraries in contemporary society